Thermal-managed oriented, multi-domain battery modelling and experimental validation. - Morganti, Manlio Valerio (Cranfield University, 2019)
A cross-domain battery simulation methodology, that could allow, a more streamlined design process, was needed. Acausal, object-oriented, multi-domain modelling strategies are becoming more and more common, beside traditional co-simulation methods, since they avoid the development of several different models for each causality type and leaving therefore flexibility to the user. A multi-domain, re-scalable, battery model and a reconfigurable battery-module test-rig are introduced in this thesis. The chosen approach allows the final user to generate different module and pack layouts from a single cell model. Materials were fully characterised, then initial conditions were defined, boundary conditions outlined and ultimately the strategy was tested against different scenarios. It is therefore possible to generate arrays of more cell models connected with each other, resulting in a module model. Such an approach achieved higher accuracy than a lumped element model with computational cost being lower than finite element models. The error in simulated voltage estimation was low and the model could handle the transient with a reduced error in temperature. In order to validate such models a test-rig, capable of hosting different battery layouts was implemented. Extensive hardware characterisation, including sensor uncertainty analysis was carried out on the experimental layout. The model of a battery module was successfully implemented. When comparing with experimental data, the discrepancies in the case of the module were larger than in the case of single cell, but the outcome was still laying in the interval of confidence. The temperature profile has been predicted well for cell and module at reduced computational costs. The case studies proved the effectiveness of cooling which was accurately captured by the models developed. Moreover, it was demonstrated that indirect liquid cooling based on removable heat cold plates can be very effective in keeping the battery module within safety operational temperatures during fast charging.
Keywords: battery; lithium-ion; thermal modelling; rescalable; test-rig; re-configurable